If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 28 + -7y = -3y Solving 28 + -7y = -3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3y' to each side of the equation. 28 + -7y + 3y = -3y + 3y Combine like terms: -7y + 3y = -4y 28 + -4y = -3y + 3y Combine like terms: -3y + 3y = 0 28 + -4y = 0 Add '-28' to each side of the equation. 28 + -28 + -4y = 0 + -28 Combine like terms: 28 + -28 = 0 0 + -4y = 0 + -28 -4y = 0 + -28 Combine like terms: 0 + -28 = -28 -4y = -28 Divide each side by '-4'. y = 7 Simplifying y = 7
| -15=-0.3k | | 4-3+x=31 | | 6a+5a+4= | | 16(18-y)+10y=240 | | -3n+13=-2n-12 | | 8x-24=2x+12 | | 2a+3o+4b=1.45 | | -4(2x-3)=3(5x-1)+15 | | 2(x-1)-2(x-4)=7(211) | | -6+9(X-2)=15x+2-6x | | 11=2y-1 | | lx-5l=8 | | 5u-u= | | -7x+9+8x=12 | | -2x+4-6x=68 | | 16m-(-6m-5)= | | n^2-8n+16=5 | | 16(y-6)+0.14y=0.10y-0.05(30) | | 7x-5y=17fory | | 7.093*100= | | 2n^2-5n=-1 | | 5x-4=2x+16 | | 54-2b=100-4b+18-6b | | -2.23*7.65= | | 0.2X+0.4x+0.6=6-9x+4 | | 4x^2-2(k+2)x+2k=0 | | 2x+6-x=2+3x-8 | | 3(x+4)+(2x+6)= | | 4x^2+x+75=0 | | 3x+5x+4-x+7=17 | | 9x+27=20-5x | | 2x^3+2=12 |